Didactic strategy for teaching digital collection management and the digitization of heritage material - Guadamuz Villalobos, Jairo Andrés (2024)
Bibliographic collections are part of the academic and cultural heritage of our society, their preservation and conservation is of utmost importance so that the information they contain can be accessible to future generations. Safeguarding information is one of the most important tasks of libraries. However, a document that must be digitized for preservation can be subjected to a lot of stress if the process is carried out with commercial scanning devices. It is for this reason that it is necessary to train future information professionals in the process of digitizing bibliographic material in a state of conservation. To achieve this, a teaching strategy was created that includes master classes on basic principles of converting analog to digital material, resolutions for each type of material, white balance and color theory. In addition, as part of the teaching strategy, videos were created that explain the proper handling of the material when digitizing, the camera configuration, the capture process, the editing of the material and the creation of an electronic document. Finally, the students participated in a virtual practical workshop where, by themselves, they completed the process of digitizing bibliographic material using what they learned in class. To evaluate the experience, an instrument was provided to the group of students who participated in the teaching strategy, thus allowing their opinion to be known about the level of approach to the topic that they may have had.